Smart Governance In Integrated Services In The Department Of Investment And One Door Integrated Services Of Makassar - Ikram Maulidin; Nasrulhaq Nasrulhaq; Lukman Anas (Department of Public Administration, Muhammadiyah University of Makassar, 2021)
ABSTRACT Smart governance is an effective realization of public services in the field of government. This study aimed to find out the application of smart governance in public services, bureaucracy, and public policy at the Makassar City Investment and One-Stop Integrated Service (DPMPTSP). In order to achieve these objectives, the research method used qualitative research methods with data collection techniques through interviews, observation, and documentation. The primary data sources were the Makassar City Investment and One-Stop Integrated Service (DPMPTSP) apparatus and the public, who had provided direct licensing services. The data had been obtained from the research result. It is processed based on the analysis technique of a descriptive qualitative approach. From the study results, it could be found that the implementation of smart governance in public services, bureaucracy, and public policies at the Makassar City DPMPTSP was still ongoing and continues to be developed. The service mechanism had been carried out online since 2019 through the Makassar City DPMPTSP official website, the bureaucratic system had run and organized effectively, and the mayor of Makassar had supported policies related to the implementation of smart governance. Keywords: Smart Governance, Integrated Services.